Pengembangan Sistem Informasi Pengelolaan Distribusi Air Bersih Berbasis Web dengan Menggunakan Metode Prototype Di Desa Cijengkol - Ahmad Fauzi; Rohmat Taufiq; Dyas Yudi Priyanggodo; Rachmat Destriana (Jurnal Teknik, 2026)
Efficient and well-organized management of clean water distribution is a crucial factor in supporting public health and community welfare. However, in practice, the management process in several regions is still carried out manually, which often leads to data recording errors, delays in information delivery, and difficulties in reporting. To address these issues, this study aims to design and develop a web-based information system for managing clean water distribution. The system was developed using the Prototype method and implemented with PHP (Laravel) as the main framework, along with MySQL, HTML, CSS, and Bootstrap technologies. The result of this study is an information system capable of facilitating customer data management, payment processing, and reporting automatically and in real time. The implementation of this system is expected to improve operational efficiency, enhance data transparency, and minimize errors in the management of clean water distribution. Therefore, this system can assist related institutions in managing clean water distribution more accurately, efficiently, and transparently.Keywords: Clean Water Distribution, Information System, Prototype, Web-Based